The Divinity Cosmological Model of Ibn al-'Arabi: The Relations between Mystical and Logic - Taufiqurrahman Taufiqurrahman (Tamaddun, 2021)
This article analyzes the cosmological model of the divinity of Ibn al-‘Arabi based on relations between mystical and logic. This research is a literature review with a descriptive analytics method. In this case, it reveals and describes as it is Ibn al-‘Arabi’s cosmological model of the divine, then analyzed and interpreted to obtain the proper data. This research finds that Ibn al-‘Arabi’s cosmological model of divine relevant to the times and is a thought that brings humans to the ‘presence’ of God. Ibn al-‘Arabi’s cosmological model of the divine is not only transcendental theological but also mysticism in character. This study is important since it reveals much deeper about the cosmological model of the divinity of Ibn al-‘Arabi. Although research on Ibn al-‘Arabi has been widely carried out including on Ibn al-‘Arabi’s divine cosmology, however, re-examining the model contained in Ibn al-‘Arabi’s divine cosmology has the potential to rediscover new reinterpretations, so that this research can be used as a foundation in the study of Islamic thought. Artikel ini menganalisis tentang model kosmologi ketuhanan Ibn al-‘Arabi yang berpijak pada jalinan antara mistis dan nalar. Penelitian ini adalah kajian kepustakaan, dengan metode deskriptif analitis. Dalam hal ini mengungkapkan dan menggambarkan secara apa adanya tentang model kosmologi ketuhanan Ibn al-‘Arabi, selanjutnya dianalisis dan dilakukan interpretasi sehingga ditemukan data yang diinginkan. Penelitian ini menemukan bahwa model kosmologi ketuhanan Ibn al-‘Arabi masih dan sangat relevan dengan zaman serta merupakan pemikiran yang membawa manusia akan ‘kehadiran’ Tuhan. Sebab model kosmologi ketuhanan Ibn al-‘Arabi tidak hanya bersifat teologis transendental semata, melainkan juga bercorak tasawuf. Penelitian ini penting karena menguak tentang model kosmologi ketuhanan Ibn al-‘Arabi secara mendalam. Walaupun penelitian tentang Ibn al-‘Arabi telah banyak dilakukan termasuk tentang kosmologi ketuhanan Ibn al-‘Arabi, namun meneliti kembali model yang terkandung dalam kosmologi ketuhanan Ibn al-‘Arabi berpotensi menemukan kembali reinterpretasi baru, sehingga penelitian ini dapat dijadikan landasan dalam kajian pemikiran Islam.